Clinical outcomes in the surgical treatment of idiopathic normal pressure hydrocephalus. (July 2016) - Shaw, Richard; Everingham, Emma; Mahant, Neil; Jacobson, Erica; Owler, Brian
Highlights: We examined clinical outcomes after ventriculoperitoneal shunting for idiopathic normal pressure hydrocephalus (INPH). Clinical improvement was observed in 85% of INPH patients. The greatest clinical improvements after shunting are in gait and motor function. INPH patients continue to improve clinically up to 12 months after shunting. Abstract: Idiopathic normal pressure hydrocephalus (INPH) is a syndrome of gait disturbance, dementia and urinary incontinence. Outcomes after ventriculoperitoneal shunting for INPH are variable due to a lack of reliable, quantitative outcome data and inconsistent methods of selecting shunt candidates. The aim of this retrospective cohort study was to assess objective and quantitative clinical outcomes of ventriculoperitoneal shunting for INPH. From 2008 to 2013, consecutive patients diagnosed with INPH based on clinical and radiological criteria were included in this single-centre study. All patients received programmable-valve ventriculoperitoneal shunts. Outcome measures were assessed at baseline, 3, 6 and 12 months post-operatively. Outcomes included gait time and scores on the Unified Parkinson's Disease Rating Scale part III (UPDRS-III), the Addenbrooke's Cognitive Examination Revised (ACE-R) and the Mini-Mental State Examination (MMSE). Thresholds for improvements were set a priori as ⩾20% decrease in gait time, ⩾10 point decrease in UPDRS-III score, ⩾5 point increase in ACE-R score and ⩾2 point increase in MMSE score at last follow-up. The proportion of patients improving varied between measures, being gait time (60%), UPDRS-III (69%), MMSE (63%), and ACE-R (56%). Overall, improvement in at least one outcome measure was observed in 85% of patients and 38% improved in gait time, UPDRS-III score and cognitive scores. Only 15% of patients experienced no improvement on any measure. This study demonstrates that the majority of INPH patients can sustain improvements in multiple symptoms up to 12 months after shunting.